Optimizing Data Center Waste Heat Reuse : Case Studies and Environmental Implications - Lü, Xiaoshu; Lu, Tao; Zhang, Qunli (Atlantis Press, 2024)
As data centers (DCs) are the backbones of information and communications technology (ICT), internet and big data, the utilization of energy by DCs has increased exponentially, which presents a significant impact on the environment. To simultaneously solve the dilemma of DC huge amount of electricity used for cooling on the one hand and a large amount of waste heat that is converted from nearly all the consumed electricity on the other hand, better use of low-grade waste heat from DCs represents a significant source of energy savings for both future fourth generation of district heating (DH) networks and reducing environmental impact. This study presents an innovative waste heat reuse approach and develops a generalizable methodology that employs a simple dynamic estimate of the potential for reutilising DC waste heat in the heat demand in DH for buildings. Brief economic calculations for building operators are also provided. The proposed modeling method is a two-stage approach for calibration and validation based on two real DCs in Finland. After validation, the model is then applied for investigating the potential environmental impacts of a real DC in its design phase. The analysis demonstrates that reusing waste heat from an 18 MW data center to heat 400,000 m2 greenhouse and buildings results in a substantial reduction of 603,366 tons of carbon dioxide (CO2) emissions over a 25-year period. From the building owners’ perspective, the payback time is remarkably short, spanning only five years. The results highlight the feasibility and effectiveness of the DC waste heat recovery to tackle the energy and environmental problems.
Keywords: Data center; Power consumption; Waste heat reuse; Simulation; Case studies; fi=Energiatekniikka|en=Energy Technology|